Asymptotic Dichotomy in a Class of Fourth-Order Nonlinear Delay Differential Equations with Damping - Chengmin Hou; Sui Sun Cheng (Abstract and Applied Analysis)
All solutions of a fourth-order nonlinear delay differential equation are shown to converge to zero or to oscillate. Novel Riccati type techniques involving third-order linear differential equations are employed. Implications in the deflection of elastic horizontal beams are also indicated.